Association between changes in predicted body composition and occurrence of heart failure: a nationwide population study - Woo, Ho Geol; Kim, Dong-Hyeok; Lee, Hyungwoo; Kang, Min Kyoung; Song, Tae-Jin (Frontiers in Endocrinology, 2023)
Background: Large population-based studies on the association between changes in body composition and the occurrence of heart failure (HF) are rare. We aimed to determine the association between changes in body composition, including the predicted body fat mass index (pBFMI), predicted appendicular skeletal muscle mass index (pASMI), and predicted lean body mass index (pLBMI), and the occurrence of HF. Methods: For present study, 1,994,042 people who consecutively underwent national health examinations from 2010~2011 (baseline period) to 2012~2013 (follow-up period) were included. The pBFMI, pASMI, and pLBMI were indirectly investigated using validated anthropometric prediction equations from the Korean National Health and Nutrition Examination Survey cohort. The outcome was defined as at least two or more claims of HF. Results: During a median of 7.59 years of follow-up, 22,172 participants (event rate, 1.09%) with HF were observed. Decreased changes in the pASMI and pLBMI were associated with the occurrence of HF among males (hazard ratio [HR] 0.952, 95% confidence interval (CI) [0.932-0.972]; HR 0.967, 95%CI [0.956-0.977], respectively) and females (HR 0.960, 95%CI [0.940-0.979]; HR 0.938, 95%CI [0.924-0.953], respectively). An increased change in the pBFMI was associated with the occurrence of HF in males (HR 1.023, 95%CI [1.001-1.044]). However, paradoxically, a change in the pBFMI was associated with the occurrence of HF in females (HR 0.913, 95%CI [0.894-0.933]). Conclusion: Decreased skeletal muscle mass was related to the occurrence of HF. However, the relationship between a change in fat mass and the occurrence of HF was different and even paradoxical depending on sex.